Terence Conran's inspiration - Conran, Terence (Conran Octopus, 2008)
Terence Conran's most personal book to date. Terence Conran, chef, restaurateur and designer, is the undisputed authority on design and his books, notably The Essential House Book, are international best sellers. A real insight in the thoughts, life and home of one of Britain's most influential designers. More than 300 full-sized colour and black and white photographs.